Bright and singular soliton solutions to the Atangana-Baleanu fractional system of equations for the ISALWs - Rezazadeh, Hadi; Adel, Waleed; Tala-Tebue, Eric; Yao, Shao-Wen; İnç, Mustafa (Elsevier, 2021)
This work searches for new soliton solutions to the Atangana-Baleanu (AB) fractional system of equations for the ion sound and Langmuir waves (ISALWs). A new auxiliary equation scheme (NAES) is implemented to solve this model with the aid of a symbolic software. The hyperbolic and trigonometric function forms of this equation have been obtained. Due to the good performance of the NAEM, it is believed that this method is a promising technique to handle a wide variety of AB fractional evolution systems. (c) 2021 The Author(s). Published by Elsevier B.V. on behalf of King Saud University. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/).
Keywords: Newauxiliary equation scheme; Equations for the ISALWs; Atangana-Baleanu fractional derivative